Knowledge, Attitude and Preventive Practices about Ebola Viral Disease among Journalists in Osogbo, Southwest Nigeria - Callistus A Akinleye; Samuel A. Olowookere; Olatunji A Olagunoye; Monisola Omoyeni Oginni; Ayoyinka Olufunmilayo Bolorunduro; Ebenezer G Adepoju (Intelektual Pustaka Media Utama, 2018)
The West African subregion presently faces the Ebola viral disease (EVD) epidemic. In order to control this epidemic, journalists need to inform the public. This study assessed their knowledge, attitude and preventive practices. A descriptive cross-sectional study was conducted among 93 journalists working in Osun State who completed a self administered questionnaire. Data collected was analysed. Mean (SD) age was 26.4±8.2 years ranging 18 to 49 years. Mean (SD) duration in practising journalism was 7.6±6.7 years (range, 1-20 years). Most had tertiary education (87.1%), were singles (74.2%), Christians (51%) and Yoruba (92.5%). Despite good knowledge (58.1%) of EVD, most had low risk perception (46.2%). The only statistical significant predictor of good knowledge was religion. In conclusion, most journalists have good knowledge but low risk perception. Efforts to improve the risk.